German arms exports and the militarisation of Arab States' foreign policies - Yannik Hüllinghorst; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2021)
Measured in terms of licenses issued, Arab states will again be among the main recipients of German military equipment exports in 2020. This continues a trend that has been evident since the early 2000s and especially since 2010, all despite Germany's recently extended ban on arms exports to Saudi Arabia. From 2018 to 2020, the value of export licences for the five most important Arab buyer countries has decreased compared to the previous period. However, their share of total export licences is still over 25 percent. In view of regional developments, this is problematic. The foreign policies of the biggest customers have changed in recent years as they become less predictable and more willing to use military means to assert their interests. Military equipment exports could thus contribute to further escalation of the numerous interstate conflicts in the Middle East and North Africa, thereby posing great risks to Germany and the EU. Against the backdrop of Germany and the EU's own export guidelines, it is therefore advised to halt exports of military products to these countries.
Keywords: 320